Analisis Pengendalian Kualitas Produk In Line untuk Meningkatkan Kelancaran Produksi di PT XYZ - Nirwani, Nurul; Yun, Yun (Universitas Batanghari Jambi, 2025)
This study aims to analyze product quality control in the production process at PT XYZ using the Statistical Process Control (SPC) method. A descriptive quantitative approach was used to collect data through direct observation of the production line, interviews with the production team and management, and secondary data from the company’s production reports from January to December 2024. SPC was applied using control charts, such as the P-chart, to monitor the percentage of product defects in real-time and detect variations in the production process. Descriptive statistical analysis was used to illustrate defect patterns and calculate the monthly average defect percentage, comparing it to the company’s tolerance limits. The results of the study show that SPC is effective in monitoring and controlling product quality, identifying variations in the production process, and implementing corrective actions to reduce defect levels. The application of SPC can improve operational efficiency and enhance product competitiveness in the international market. This research contributes to the development of statistical data-based quality control systems, which can be adopted by other garment companies in Indonesia to improve product quality and production efficiency.